Cyber mage : a novel - Hossain, Saad Z. (The Unnamed Press, 2021)
"Speculative fiction novel set in post-apocalyptic Dhaka, Bangladesh in 2089, after residents have discovered how to survive with biological nanotech. Cyber Mage, the teenager moonlighting as a hacker, crosses paths with mercenary Djibrel and together they seek out the fate of the Djinn, a magical super race of genies"--